Hubungan Beban Kerja Mental dan Lingkungan Kerja Non-Fisik dengan Stres Kerja di UMKM Sanan - Vina Aprilia; Moch. Yunus; Anita Sulistyorini; Marji Marji (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
UMKM Sanan Tempe Chips is one of the main informal industries in Malang City. The amount of tempe chips marketing can increase the production target that must be achieved per day. Based on the preliminary studies, it was found that 6 out of 9 workers had complaints dizziness, back pain, irritability, and boredom at work. These complaints can be signs of job stress. Factors that cause job stress are mental workload and non-physical work environment. This study aims to determine the relationship between mental workload and non-physical work environment with job stress in UMKM Sanan Tempe Chips. The research population consisted of 136 people with a sampling determination that used the Lemeshow formula, and a sample of 56 people was obtained. The Spearman Rank test was used in bivariate analysis. The results of the study indicated that the two independent variables had significant relationship with the dependent variable (job stress). The mental workload variable had a value (p=0.026), while the non-physical work environment variable had a value (p=0.035). In an effort to reduce job stress levels, it is hoped that superiors can routinely rotate the workers and always monitor employee performance and establish closeness between workers in the work environment.